Donation-Based Crowdfunding Innovation in Promoting Sustainable Islamic Microfinance: A Literature Review - Akhmad Affandi Mahfudz; Rusyda Afifah Ahmad; Helmy Fauzy Ahmad; Penta Shahifah Dena (Universitas Muhammadiyah Yogyakarta, 2025)
The purpose of this study is to analyze the efforts to implement the CrowdFunding Platform model as a new face of Islamic philanthropy for the development of Islamic microfinance. This study uses a qualitative method with a contextual approach. Issues such as lack of access to financial services, lack of funding, and cultural barriers can be potential influences and future prospects for innovative and sharia-compliant social crowdfunding models in Islamic microfinance. The results of this study emphasize that the sharia social crowdfunding model must pay attention to sharia principles, transparency, accountability, community involvement and regulatory support. The implications of this study are the potential for developing social resources is very effective and requires continuous innovation, especially if the social funds collected can be managed by institutions and collaborating with the government can support improving the lives of poor people with the challenges of technological advances that attract public trust in the sharia crowdfunding system. Thus increasing the reputation of trust in sharia financial institutions in managing Islamic philanthropic funds. While the novelty in this study is an in-depth analysis of multi-sector collaboration between the government, financial institutions and the community which is a new element in strengthening sustainable and inclusive Islamic microfinance in Indonesia.